Molecular insights into the bidirectional link between anxiety and COVID-19: a combined clinical and bioinformatics approach - Huang, Wenjie; Hu, Biao; Gu, Chengyu; Wu, Hao; Huang, Yize; Yang, Dexiang (Frontiers in Psychiatry, 2025)
IntroductionNumerous studies have reported an increased incidence of anxiety in individuals affected by COVID-19; however, the specific molecular mechanisms underlying this association remain poorly understood.MethodsIn this study, we employed the Zung Self-Rating Anxiety Scale (SAS) to assess anxiety levels in 36 asymptomatic COVID-19 patients. In parallel, we conducted a comprehensive literature-based data mining analysis to reconstruct the functional and molecular pathways linking COVID-19 and anxiety. Additionally, we performed a meta-analysis using eight independent COVID-19 case–control gene expression datasets to examine expression alterations in the literature-derived pathways.ResultsOur findings revealed that even among asymptomatic individuals, approximately 25% exhibited mild anxiety symptoms, which negatively correlated with age. The reconstructed pathways suggested that COVID-19 may contribute to cognitive decline through multisystem dysfunction and structural or functional brain abnormalities—hallmarks of anxiety disorders. The meta-analysis confirmed increased expression of four anxiety-related molecular mediators in response to COVID-19 infection: CALCA, TNF, PLAT, and PPARG, with the latter three associated with neurocognitive decline.ConclusionThese results provide molecular-level evidence for a bidirectional association between COVID-19 and anxiety, potentially mediated by dysregulated inflammatory cytokines and other secreted proteins. Furthermore, impaired cognitive function may serve as a critical link connecting these two conditions.